Attribution in international law and arbitration - Stefano, Carlo De (Oxford : Oxford University Press, 2020)
This volume clarifies and critically discusses the international rules of attribution of conduct, particularly regarding their application to states under international investment law. It examines the key question of how and to what extent breaches of State obligations, particularly in respect of States' commitments to foreign investors under international investment agreements (IIAs) and bilateral investment treaties (BITs), can be attributed. Of special interest within this context is the responsibility of States when the alleged breach has been committed by separate legal entities, rather than the state itself. Under domestic law, entities such as state-owned enterprises (SOEs) are considered legally distinct, however the State may still be considered responsible for their actions under international law.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 7, 2020).
Keywords: International commercial arbitration; Investments, Foreign (International law); Law; Laws of specific jurisdictions & specific areas of law